DEFENSE MECHANISMS AND COUNTER-REFERENTIAL ASPECTS OF THE CAREGIVER: CONTRIBUTIONS FROM PSYCHOANALYSIS AND HEALTH PASTORAL CARE - Chagas Ramos , Rawy (Health and Society, 2025)
This article investigates the defense mechanisms and countertransference processes inherent in the caregiver’s experience in hospital and pastoral settings. Drawing on classical and contemporary psychoanalytic frameworks (Freud, Anna Freud, Melanie Klein, Winnicott, and Vaillant) and the dialogue with Catholic spirituality (Koenig and the Pastoral Care of Health documents), the study aims to understand how these psychic defenses, although initially protective, may undermine the authenticity, mental health, and spiritual well-being of those who care. The paper offers theoretical and practical contributions to help caregivers recognize their own vulnerabilities, integrate their psychic and spiritual dimensions, and sustain an ethical, compassionate, and humanized approach to care. This study originates from pastoral and clinical experiences at the Hospital Federal de Bonsucesso and a lecture delivered at the Health Pastoral Care Meeting of the Archdiocese of Rio de Janeiro.